Nonalcoholic fatty liver disease as a predictor of atrial fibrillation: a systematic review and meta-analysis - Zhou, Yaqiong; Lai, Chenglin; Peng, Chunrong; Chen, Mingyue; Li, Bolin; Wang, Xiaoyun; Sun, Jingjing; Sun, Chaofeng (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : Numerous epidemiologic studies have investigated the link between nonalcoholic fatty liver disease (NAFLD) and long-term atrial fibrillation (AF) risk, but the results are surprisingly conflicting. Aim : Therefore, we systematically reviewed all published studies assessing the risk of AF in patients with NAFLD and conducted a meta-analysis. Material and methods : We performed a literature search using PubMed, EMBASE and Cochrane Library databases in February 2017 with no restrictions. Two cohort studies and two cross-sectional studies were identified, involving a total of 5150 subjects (NAFLD: 1655; controls: 3495) in this meta-analysis. Data from selected studies were extracted and a meta-analysis was performed using a random effects model. Results : Nonalcoholic fatty liver disease patients had a significantly higher risk of AF compared to controls (relative risk (RR): 2.61; 95% confidence interval (CI): 1.34–5.06, p = 0.00; I2 = 52.5%, p = 0.097). In a further analysis stratified by presence of type 2 diabetes, the increased risk was present predominantly in patients with type 2 diabetes (RR = 5.10; 95% CI: 2.43–10.7, p < 0.001; I2 = 0, p = 0.958). However, subjects without type 2 diabetes were at slightly increased risk of AF but the relative risk did not reach statistical significance (RR = 1.68; 95% CI: 0.99–2.82, p = 0.05; I2 = 0, p = 0.461). Conclusions : Our meta-analysis suggested that ultrasound-diagnosed NAFLD patients have a significantly higher risk for AF after adjustment for numerous important clinical risk factors for AF. These results need to be confirmed in large prospective studies.